Sosialisasi Pergeseran Pola Pangan Akibat Gastro-Kolonialisme di Kampung Baidub - Mutiya Oktariani; Sri Hanifah; Ratu Bulkis Ramli; Damayanti Damayanti; Ismail Ismail; Parman Parman; Mudatsir Mudatsir (Jurnal Pengabdian Dian Mandala, 2024)
This community service aims to socialize the shift in food patterns akinat gastro-colonialism in Baidub Village, Merauke. Gastro-colonialism has led to significant changes in people's food patterns from consumption of local foods such as sago, yam, and maize, to rice and processed foods. This has an impact on people's health and culture. This community service is carried out by community service methods, namely socialization to 300 residents of Baidub Village. Socialization materials include shifts in food patterns, the concept of gastro-colonialism, and the nutritional content of sago and processed foods. The results of community service show that the people of Baidub Village enthusiastically participated in socialization and began to understand the negative impact of gastro-colonialism. They are also motivated to return to eating local food, especially sago.